2011
DOI: 10.1007/s10903-011-9517-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Myth of the “Model Minority”: A Participatory Community Health Assessment of Chinese and Vietnamese Adults

Abstract: Despite the persistent belief that Asians are the "model minority" there is accumulating evidence of health concerns within Asian subgroups. In this study, we implemented a cross-sectional participatory community health assessment in an urban city in Massachusetts, to understand differences and similarities in demographics, health and healthcare access in Chinese and Vietnamese adults. We gathered qualitative data from community stakeholders to inform the development of a community health assessment tool. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Loss to followup, which contributes to inflated survival estimates, may occur because of the return of immigrants with serious illnesses to their countries of origin to die, a phenomenon known as the salmon bias [47,48]. However, studies thus far indicate that salmon bias has limited impact on Asian American survival, likely due to travel being too distant and time-consuming for gravely ill individuals to undertake [49,50]. Lastly, some important covariates, such as residual tumor category, comorbidities, and postoperative complications, are critical factors impacting gastric cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…Loss to followup, which contributes to inflated survival estimates, may occur because of the return of immigrants with serious illnesses to their countries of origin to die, a phenomenon known as the salmon bias [47,48]. However, studies thus far indicate that salmon bias has limited impact on Asian American survival, likely due to travel being too distant and time-consuming for gravely ill individuals to undertake [49,50]. Lastly, some important covariates, such as residual tumor category, comorbidities, and postoperative complications, are critical factors impacting gastric cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…Such a possibility would be consistent with previous work suggesting that the Bmodel minority myth^and other stereotypes may impede clinician recognition of common health problems in Asian Americans (e.g., hypertension, dementia). [30][31][32] Similarly, clinicians may be less likely to recognize or respond to obesity in Asian American patients compared to other adults. In potential support of this hypothesis, we found that among adults aged ≥ 45 years, the magnitude of the disparity in diabetes screening was unexpectedly widest for obese adults.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Many prior studies have aggregated outcomes for the entire Asian American population; aggregated analyses may fail to detect important disparities for some subgroups. [11][12][13][14] Further, they have used data predating the implementation of the ACA, which attempted to reduce disparities in access to and affordability of care through expansion of Medicaid eligibility, availability of parental coverage for dependents 26 and under, and reducing cost-sharing for routine preventive visits. Asian Americans made sizable gains in coverage following the insurance expansions in 2014, but substantial variations in rates in uninsurance remained across subgroups.…”
Section: Introductionmentioning
confidence: 99%